Digitalization of Employee Cooperative Loan Applications - Suwandi, Suwandi; Asfi, Marsani; Novelia, Belinda; Gitama, Gytha Nurhana Dhea Praadha (Proceeding International Conference on Religion, Science and Education, 2024)
Employee cooperatives are a type of cooperative founded and owned by employees or workers of a company or organization. In the operational activities of employee cooperatives, cooperative members usually consist of active or retired employees who work in the same company. Each member has the right to participate in managing the cooperative, including making decisions regarding business activities and cooperative policies. The objectives of this research are: (1) implementing digitalization of employee cooperative loan applications, (2) creating employee cooperative loan transaction reports, (3) creating internal control in an institution's employee cooperative through digitalization. The method used in this study is the waterfall method. The result of this research is a web-based employee cooperative loan application. The reports formed from this application are loan application forms, loan application reports, loan approval reports, loan cards, funds disbursement receipts, journals when funds are disbursed and journals when receiving instalments.